INFORMATION MANAGEMENT OF PRODUCTION RAW MATERIALS INFORMATION WITH FIFO METHOD BASED ON CLIENT SERVER - Agus Waryanto; Rohmad Haryadi (LITERACY : International Scientific Journals of Social, Education, Humanities, 2022)
Information technology that is used properly will have a good influence on the company, among others, can increase productivity, work efficiency and of course very useful for institutions such as Koperasi Kawi Mandiri Sentosa in facing competitive business competition. The determination and speed of data processing from Koperasi Kawi Mandiri Sentosa, the presentation of fast, precise and accurate information will make it easier for companies to make the right decisions as well. Koperasi Kawi Mandiri Sentosa has a variety of fund products which include Voluntary Deposits and Time Deposits. As well as credit products which include Monthly Loans and Term Loans, while the procedures to be processed consist of the savings section, and the credit loan section. If there is a deposit transaction, it can be recorded in the customer's proof of deposit and at the same time the data can be saved to the computer automatically. Likewise, if there is a loan transaction from a customer, the data on the computer can be known with certainty and accuracy. The program that will be developed by the author is a multiuser-based savings and loan accounting information system, the software used is Microsoft Visual Basic 6.0